Trade in floodplain medieval settlements of the Lower Kama region in the XII–XIV centuries (based on the finds of metal mirrors) - Rudenko Konstantin A.; Kazakov Evgeniy P. (Поволжская археология)
The article is dedicated to the study of trade relations in the late Volga Bolgaria and the Bolgar region of the Golden Horde in the XII–XIV centuries. The basis for this study was a collection of fragments of metal mirrors found on the settlements, located in the floodplain of the Kama River and its tributaries. These are the settlements on Semenovsky Island, settlements – Komintern III, Laishevo, Murzikha. All these finds are from the collapsed cultural layer, as these archaeological sites were destroyed by the Kuibyshev reservoir from the middle of the XX century and now they do not exist. A total of 17 pieces of fragments of metal mirrors of XII–XIV centuries from the Museum of Archaeology of the Institute of Archaeology of the Tatarstan Academy of Sciences were investigated. The largest number of these artifacts are 6–7 cm in diameter and undecorated. This group of mirrors also includes items with geometric images. These mirrors are associated with nomads. Mirrors with complex compositions, for example, running wild animals, as well as copies of Chinese mirrors with dragons and wise men, are rare. Mirrors were brought from Bolgar, where some of them were made. But some of the items, especially those of nomadic traditions, were made locally – at settlements in the floodplain. Not only whole mirrors were brought, but also fragments – for jewelry craftsmen who used them to add to alloys. It should be noted that the composition of mirrors at each of the considered settlements was different.